POLITICAL EMPOWERMENT OF MUSLIM WOMEN IN KAMILA SHAMSIE’S HOME FIRE: A COMPARATIVE STUDY OF ISMA AND ANEEKA (Contemporary Journal of Social Science Review, 2025)
This research article reviews Kamila Shamsie’s  Home Fire (2017)  through a postcolonial-feminist perspectives, exploring the interplay of political empowerment and disempowerment in the lives of twin sisters, Isma and Aneeka. This research analyzes the effects of family structures, societal expectations, and governmental power on the twin sister’s sense of their own political agency. Applying qualitative textual analysis, the study identifies the complicated intertwine between gender, governance, and postcolonial settings in current literature. Findings show that both sisters Isma and Aneeka employ different strategies to cope with male-dominated and postcolonial systems: Isma’s awakening is subtle, framed by familial duties, while Aneeka’s bold political stances confronts both state and societal power. The research emphasizes the complicated realities of female’s political awakening in postcolonial settings and adds to feminist literary discourse by investigating the interplay of gender, governance, and diaspora individuality.